Digital Literacy Skill Development Model for Undergraduate Students, Rajabhat University in the Northeast - Arpamo, Phannathonnat; Duangchatom, Kritkanok; Phoojomjit, Pongphop (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to 1) study the components and indicators of digital literacy skills of undergraduate students of Rajabhat Universities in the Northeast, 2) study the current conditions, desired conditions and needs for the development of digital literacy skills of undergraduate students of Rajabhat Universities in the Northeast, 3) create and develop a digital literacy skills development model for undergraduate students of Rajabhat Universities in the Northeast, and 4) study the results of a tryout of the digital literacy skills development model for undergraduate students of Rajabhat Universities in the Northeast. The research was divided into 4 phases. Phase 1 studied the components and indicators of digital literacy skills. The research tool was an interview form. The target group for the study consisted of 9 experts to confirm the components and indicators. Phase 2 studied the current conditions, desired conditions, and needs of digital literacy skills. The sample consisted of 275 undergraduate students in the second semester of the academic year 2023, from 11 Rajabhat Universities in the Northeast. The research tool was a questionnaire with a total reliability of .87. Data analysis employed the mean and standard deviation. Phase 3 created and developed a digital literacy skills development model. The target group consisted of 9 experts to confirm and assess suitability, feasibility and usefulness of the model. Phase 4 studied the results of the tryout with the digital literacy skills development model. The target group consisted of 30 undergraduate students of Rajabhat Maha Sarakham University. The statistics used in the research included percentage, mean, standard deviation, and Priority Needs Index (PNImodified). The results of the research revealed that 1) the components and indicators of digital literacy skills of undergraduate students of Rajabhat Universities in the Northeast consisted of 5 components and 18 indicators, including (1) creative skills, (2) practical skills, (3) communication skills, (4) accessibility skills, and (5) assessment skills; 2) the current state of developing digital literacy skills, on the whole, was at a high level (x = 3.47). The desired conditions of digital literacy skills development, on the whole, were at the highest level ( x= 4.73); the need for developing digital literacy skills, on the whole, had a PNI Modified value of 0.34 (PNImodified = 0.34); 3) the digital literacy skills development model had 5 components: principles, objectives, content, processes, and measurement and evaluation. There were 5 learning modules: Module 1: Creative Skills; Module 2: Practical Skills; Module 3: Communication Skills; Module 4: Accessibility Skills; and Module 5: Assessment Skills. The results of assessing the appropriateness, feasibility, and usefulness of the model for developing digital literacy skills, on the whole, were at the highest level ( x = 4.82). 4) The results of using the digital literacy skills development model, on the whole, were at the highest level ( x = 4.62). The satisfaction of the target group with the digital literacy skills development model, was at the highest level ( x = 4.81).